PARENTS OF PAEDIATRIC LIVER TRANSPLANT PATIENTS—OPINIONS AND EXPERIENCES OF MEDICATION ISSUES. Issue 8 (11th July 2014) - Gutermann, L; Sharif, K; Rieutord, A; Terry, D
Abstract : Aim: To identify the opinions and experiences of carers of post-transplant liver patients concerning medication. Although transplantation is perceived as a new chance of life, post-transplant medications are often felt as a constraint that can be difficult to manage. To improve clinical practice and to support families' needs, the objective of this project was to identify the main medication issues encountered by children and their parents, in order to find suitable means to improve their care management. Method: Self-completed or telephone-completed 30 point anonymised multi-factorial cross-sectional survey, single-site. A questionnaire was designed to obtain parents' experiences in the last 12 months. A cognisance test was conducted with 4 parents and the survey instrument modified accordingly. Parent-carers of children transplanted from January 2011 were recruited following two strategies 1-self completion during clinic attendance at the outpatient department over a period of 4 weeks during May 2013, 2-telephone completion by randomisation of 30 parents. Survey included: obtaining, administering and monitoring medicines, side-effects and training. Results: 37 parents were recruited (80.3%). Medication supply problems concerned 32.4% (n=12) of parents. The main problem was that the General Practitioner declined to prescribe the medicine(s) required (35.3%). 81.1% (n=30) of parents declared that they have almost run out of medicines but no children missed a dose because of supply problems. 24.3% (n=9) of parents experienced medication administration problems (usually vomiting n=7). Regarding medicine-related blood tests, 37.8% (n=14) of parents were concerned and reported that obtaining the results was the main issue (n=6). Parents had also problems related to side-effect management, with 56.6% (n=21) of respondents who declared that their child had side-effects in the last year and 37.7% (n=14) of respondents felt that they have an inadequate knowledge on how to manage side-effects. Concerning parents' opinions of their current training, 81.1% (n=30) of them thought that the service was excellent or very good and 97.5% (n=36) thought that the presentation of the patient support information was comprehensible and accurate. Finally, among proposed service improvements, parents' preferences were for an online learning tool on medicines, a comic book to explain transplantation and medicines to the child, and the opportunity to have pharmaceutical consultations. Conclusion: This study provides an understanding of the issues encountered with post-transplant medication management, and describes the parents' perspectives in order to evolve our practice according to their real needs. Numerous medicines related problems were identified. However, the current multidisciplinary team (including doctors, specialist nurses and pharmacy staff) seem effective in preventing children from missing doses. Due to the problems reported concerning adverse drug effects the development of thorough information sessions for parents in this domain should be considered. Although parents seemed particularly satisfied by the current training, many experienced issues linked to post-transplant medication management. Thus, service improvements are envisaged and a working party is currently considering service development options.